2022
DOI: 10.1101/2022.05.30.493996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct activation of an innate immune system in bacteria by a viral capsid protein

Abstract: Bacteria have evolved sophisticated and diverse immunity mechanisms to protect themselves against a nearly constant onslaught of bacteriophages. Similar to how eukaryotic innate immune systems sense foreign invaders through pathogen-associated molecular patterns (PAMPs), many bacterial immune systems that respond to bacteriophage infection require a phage-specific trigger to be activated. However, the identities of such triggers and the mechanistic basis of sensing remain almost completely unknown. Here, we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The other 11 defense systems have morphotype-specific activities, targeting one (myophage-specific Druantia Type III and IetAS) or two phage morphotypes. This is in line with the sensing of specific conserved phage proteins, such as the capsid or terminase proteins, to trigger an immune response 2628 .…”
Section: Resultssupporting
confidence: 61%
“…The other 11 defense systems have morphotype-specific activities, targeting one (myophage-specific Druantia Type III and IetAS) or two phage morphotypes. This is in line with the sensing of specific conserved phage proteins, such as the capsid or terminase proteins, to trigger an immune response 2628 .…”
Section: Resultssupporting
confidence: 61%
“…A second major category of escape mutations involves mutations in phage structural genes (Figure 3, Figure 6). For example, mutations in the phage capsid protein enable various phages to overcome the defense systems SEFIR (Figure 3B, Table S2), Pycsar (Tal et al, 2021), some types of CBASS (Huiting et al, 2022), PifA (Molineux et al, 1989), Lit (Champness and Snyder, 1982), and CapRel SJ46 (Zhang et al, 2022). Most of these systems function via abortive infection, but at least in the case of CBASS, Pycsar and SEFIR, co-expression of the wild-type form of the major capsid protein with the defense system did not activate toxicity of the system (Figure S3A) (Huiting et al, 2022; Tal et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Although we show that expression of each individual phage protein triggers the respective defense system, our data does not reveal whether this triggering is by direct interactions of the phage protein and the defense system or by an indirect effect. Previous studies have identified defense systems that are activated by direct binding to a phage protein, as in the case of DSR2 (Garb et al, 2021) and CapRel (Zhang et al, 2022). On the other hand multiple defense systems are known to sense the effect of the phage protein and not the protein itself, for example retrons Ec48 and Se72 that sense RecBCD inhibition (Millman et al, 2020; this study), as well as PrrC that is triggered upon sensing the inhibition of a restriction enzyme by phages (Penner et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phage adsorption assay we performed as we reported recently with minor modification 53 . Briefly, 2 ml of culture was collected at OD 600 ∼ 1 and mixed with different amounts of phages (10 7 -10 9 PFU/ml) to reach a MOI of 0.01. Then the phage and cell mixtures were cultured at 37°C for 10 min to allow phages to adsorb to the cells, and supernatants were plated to quantify PFUs before and after adsorption.…”
Section: Methodsmentioning
confidence: 99%